CONSTITUENTS AND ANTIBACTERIAL ABILITY OF WATER BUG (Lethocerus indicus Lep.) ESSENTIAL OILS - Van Loi, Nguyen; Thi Hanh, Do; Hoang Nam, Pham (HNUE Journal of Science: Journal of Natural Sciences, 2025)
The water bug, Lethocerus indicus Lep., is an aquatic insect commonly found in deep rice fields, lakes, ponds, and rivers in Vietnam. In this study, male specimens were collected from fields, ditches, ponds, and lakes in Dai Cuong commune, Ung Hoa district, Hanoi, Vietnam. The objective of this study is to determine the constituents and antibacterial properties of the essential oil extracted from L. indicus. Gas chromatography–mass spectrometry (GC-MS) analysis identified fifteen major components, primarily hydrocarbons and oxygenated hydrocarbons. In which, specifically, the essential oil comprised 12.41% monoterpenes, 25.12% sesquiterpenes, 21.98% alcohols, 1.79% aldehydes, and 36.63% esters. In particular, (E)-2-hexenol-acetate was the predominant component, accounting for 36.63%, and is believed to contribute to the characteristic aroma of the essential oil. The antibacterial activity of the essential oil was evaluated against six microorganisms: Staphylococcus aureus, Clostridium botulinum, Clostridium perfringens, Escherichia coli, Campylobacter jejuni, and Vibrio parahaemolyticus.